Evidence assessment and narrative synthesis of the key characteristics of older people living in service-integrated housing facilities, and their 'accommodation journey'. Issue 1 (25th November 2021) - Thompson, Juliana; Hill, Michael; Bainbridge, Lesley; Cowie, Daniel; Flewers, Emma
Abstract : Purpose: This paper aims to provide an evidence assessment and narrative synthesis of literature regarding the key characteristics of older people living in service-integrated housing (SIH) facilities and their "accommodation journey". Design/methodology/approach: A rapid evidence assessment was conducted: 22 research publications met the inclusion criteria and were analysed using narrative synthesis. Findings: The quality of studies in this area is low, but consistency across components of the results of studies included in the review is apparent. Results suggest key characteristics of older people that drive moves into SIH are a decline in health, increased dependency, increased health service use and carer burden. Suggested key characteristics of SIH residents are high levels of health problems, dependency and health service use, but high self-reported health and well-being. Results indicate that the key driver for older people leaving SIH is a lack of workforce competency to manage further declines in health and dependency status. Research limitations/implications: Current policy may not realise or account for the complex health and care needs of SIH residents. Investment into integrated care, robust community health services and workforce development to facilitate a comprehensive assessment approach may be required to support residents to remain in SIH and live well. Further longitudinal studies are required to map the progression of SIH residents' health status in detail over time to provide an understanding of preventative and enablement support, development of care pathways and workforce planning and development requirements. Originality/value: This evidence assessment is the first to consider the accommodation journey of older people residing in SIH.